O GERENCIAMENTO DE RESULTADOS E SUA RELAÇÃO COM O ENDIVIDAMENTO DE EMPRESAS BRASILEIRAS DE CAPITAL ABERTO - LEONE, FÁTIMA PENHA (2016)
This study aimed to verify the existence of relationship between the indebtedness of companies and the earnings management, trying to analyze if the debt influences somehow this kind of practice used by companies in order to change the perception of users of accounting statements. The objective includes: (i) to verify if companies with higher debt levels incurred with greater intensity in the earnings management practice; ii) to identify whether the companies practiced earnings management in the period prior to fundraising through debentures or financial debt; (iii) check for differences in earnings management practices in companies that own debentures and those that do not have debentures; and (iv) to investigate whether there is difference in the practice of earnings management regarding short-term or long-term debts. The sample was collected in the Economatica database, considering the period from 2008 to 2015. After using Model KS (1995) and Model Dechow et al (2012) it was possible to verify the relationship between earnings management practices and indebtedness of companies. A positive relationship between the short-term financial debts and the earnings management practices was found, suggesting that companies with higher debt levels close to maturity, would have a greater concern with funding costs. As for the long-term debt, no relationship was found between the variables, denying the expectation that companies that need third-party capital to maintain their operations manage results to meet requirements linked to contracts loans. Regarding total indebtedness, relationship between debt and management results was found, indicating that companies incur in earnings management practice to change the perception of risk and raise funds with lower rates.